2017
DOI: 10.3892/etm.2017.4255
|View full text |Cite
|
Sign up to set email alerts
|

miR-148a Suppresses estrogen-induced viability and migration of breast cancer cells via inhibition of estrogen receptor α expression

Abstract: Abstract. MicroRNAs (miRs) play critical roles in the development and malignant progression of human cancers. miR-148a has previously been found to inhibit the migration and invasion of breast cancer cells. However, the underlying mechanism of miR-148a in regulating the viability and migration of estrogen receptor (ER) α-positive breast cancer cells is still unknown. In this study, ERα-positive breast cancer MCF7 cells were treated with estradiol (E2). Data from MTT and wound healing assays showed that E2 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…On the other hand, it was found that miR-148a can be regulated via estrogen receptors, i.e. GPER and ERα 44,45 . In turn, expression changes observed in the case of miR-592 seem to be directly related with a decrease of nuclear estrogen receptors level.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was found that miR-148a can be regulated via estrogen receptors, i.e. GPER and ERα 44,45 . In turn, expression changes observed in the case of miR-592 seem to be directly related with a decrease of nuclear estrogen receptors level.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of observational studies investigated the prognostic significance of miR-148a in various cancers and reported a correlation between low miR-148a levels and poor overall survival in patients with cancer (6). miR-148a has been found to be dysregulated in several cancers, including ovarian cancer (7), breast cancer (8,9), colorectal cancer (10), gastrointestinal cancer (11), prostate cancer (12), hepatocellular carcinoma (13), papillary thyroid carcinoma (14) and renal cancer (15). In ovarian cancer, miR-148a is decreased in the plasma of patients compared with healthy controls and its expression level is positively associated with survival time (16).…”
Section: Introductionmentioning
confidence: 99%
“…The present in vitro study revealed that overexpression of microRNA-148a reduced ERα, PI3K and p-AKT protein expression levels in osteoblasts in vitro. Ma et al previously reported that microRNA-148a suppresses estrogen induced viability and migration through ERα expression in breast cancer cells (23). Zhang et al suggested that microRNA-148a promotes cancer cell growth by targeting PI3K/Akt protein expression in osteosarcoma (24).…”
Section: Discussionmentioning
confidence: 99%